2021
DOI: 10.1097/mat.0000000000001340
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin Dose Optimization in Extracorporeal Membrane Oxygenation in Infants

Abstract: Anticoagulation in extracorporeal membrane oxygenation (ECMO) is challenging, with significant morbidity and mortality associated with thrombotic complications. Unfractionated heparin (UFH) is commonly used, which depends on native antithrombin (AT) function to exert anticoagulant effects. Antithrombin deficiency is common in infants on ECMO and replacement with AT concentrate may be warranted. However, dosing recommendations in this population are limited. We conducted a retrospective review of patients <1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Summary of evidence. Nineteen studies reporting on AT use were included in the analysis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The major themes that emerged from these studies include: 1) AT activities were low at initiation of ECMO; 2) AT activity increased after AT administration but the dose response was variable; 3) the association between AT administration and heparin dose rate and coagulation monitoring parameters was mixed but most studies showed no association; and 4) association between AT and clinical outcomes was mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Summary of evidence. Nineteen studies reporting on AT use were included in the analysis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The major themes that emerged from these studies include: 1) AT activities were low at initiation of ECMO; 2) AT activity increased after AT administration but the dose response was variable; 3) the association between AT administration and heparin dose rate and coagulation monitoring parameters was mixed but most studies showed no association; and 4) association between AT and clinical outcomes was mixed.…”
Section: Resultsmentioning
confidence: 99%
“…We read with great interest the Brief Communication by Seelhammer et al in response to our manuscript “Antithrombin Dose Optimization in Extracorporeal Membrane Oxygenation in Infants”. 1 The authors write in support of direct Thrombin inhibitors (DTI) as alternatives to unfractionated heparin (UFH) for the systemic anticoagulation of patients supported by extracorporeal membrane oxygenation (ECMO). Because anticoagulation with UFH requires a multitude of laboratory tests and sufficient levels of the cofactor antithrombin for effect, they suggest the time may be right for DTIs to replace UFH as the first line anticoagulant for adult and pediatric patients supported on ECMO.…”
Section: To the Editormentioning
confidence: 99%
“…1 With this in mind, we read with great interest the salient study by Liviskie et al investigating the effectiveness of AT dosing equations to predict postdose AT levels in a cohort of 41 pediatric patients under 1 year of age. 2 Important findings included a low baseline mean AT level of 43% (±13%) and mean postdose AT level of 52.6% (±14.2%) with poor correlation using weight-based dosing equations (R 2 = 0.082) that improved with integration of desired change in AT level from baseline augmented with adjustments of the patients' weight supplemented with an adaptation utilizing the estimated weight from the volume of the ECMO circuit (R 2 = 0.427). We applaud the authors for providing highly granular detail on AT dosing on a relatively large number of infant ECMO patients along with the concurrent analysis leveraging a robust quantity of prediction equations that included commonly accepted as well as manufacturer recommended and institutional adjusted calculations.…”
mentioning
confidence: 99%